STRUCTURAL AND COMPOSITIONAL EVOLUTION OF CR/FE SOLIDS AFTER INDIRECT CHROMATE REDUCTION BY DISSIMILATORY IRON-REDUCING BACTERIA - Hansel C.M.; Fendorf S.; Wielinga B.W. (My University, 2003)
The mobility and toxicity of Cr within surface and subsurface environments is diminished by the reduction of Cr(VI) to Cr(III). The reduction of hexavalent chromium can proceed via chemical or biological means. Coupled processes may also occur including reduction via the production of microbial metabolites, including aqueous Fe(II). The ultimate pathway of Cr(VI) reduction will dictate the reaction products and hence the solubility of Cr(III). Here, we investigate the fate of Cr following a coupled biotic–abiotic reduction pathway of chromate under iron-reducing conditions. Dissimilatory bacterial reduction of two-line ferrihydrite indirectly stimulates reduction of Cr(VI) by producing aqueous Fe(II). The product of this reaction is a mixed Fe(III)-Cr(III) hydroxide of the general formula Fe1−xCrx(OH)3 · nH2O, having an α/β-FeOOH local order. As the reaction proceeds, Fe within the system is cycled (i.e., Fe(III) within the hydroxide reaction product is further reduced by dissimilatory iron-reducing bacteria to Fe(II) and available for continued Cr reduction) and the hydroxide products become enriched in Cr relative to Fe, ultimately approaching a pure Cr(OH)3 · nH2O phase. This Cr purification process appreciably increases the solubility of the hydroxide phases, although even the pure-phase chromium hydroxide is relatively insoluble.